KINERJA PEGAWAI DI KANTOR CAMAT KAMPA KABUPATEN KAMPAR - Riski Sulaiman; Khairul Amri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The inaccuracy in the completion of the files entered at the Kampa District Office of Kampar Regency is that the employees are not in place and the vacancies of service employees, causing the service to take longer than the specified time. In addition, the length of the correspondence process is due to the absence of employees at the Kampa District Office, Kampar Regency. This study aims to describe the performance of employees at the office of the Camat Kampa, Kampar Regency. To define the factors that affect the performance of employees at the office of the Camat Kampa, Kampar Regency. The formulation of the problem in this research is how is the performance of employees at the office of the Camat Kampa, Kampar Regency? What are the factors that affect the performance of employees in the office of the Camat Kampa, Kampar Regency? The research method used in this study is this research using a qualitative approach. The research location is at the Kampa District Office, Kampar Regency. The research informants were the Head of the Kampa District of Kampar Regency, the Secretary of the Head of the Kampa District of Kampar Regency, the Head of Administration, and the Community of the Kampa District, Kampar Regency. Based on the results of research and discussions that have been carried out in the previous chapter related to the performance of employees at the Kampa sub-district office, Kampar Regency, it can be concluded that the employee performance at the Kampa sub-district office can be seen from the lack of job responsibilities that must be given to the community in providing appropriate service delivery tasks. pretty good. Keywords: Performance, Employees, and the Camat Office